2008
DOI: 10.1097/ede.0b013e318181b3ca
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Traffic-Related Air Pollution and Lung Cancer Risk

Abstract: We found evidence for an association of exposure to black smoke and traffic with lung cancer incidence in people who had never smoked. No associations were found for the full cohort, or for other categories of smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
154
3
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(165 citation statements)
references
References 24 publications
6
154
3
2
Order By: Relevance
“…None of these studies considered multipollutant models. Beelen et al (2008) presented the detailed results for one of the cohorts included in the ESCAPE study, a study of approximately 115,000 Dutch subjects. They examined the relationship between lung cancer and PM 2.5 and BC.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…None of these studies considered multipollutant models. Beelen et al (2008) presented the detailed results for one of the cohorts included in the ESCAPE study, a study of approximately 115,000 Dutch subjects. They examined the relationship between lung cancer and PM 2.5 and BC.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…Beelen et al (2008) found evidence for an association of exposure to black smoke with lung cancer incidence in people who had never smoked. The BC exposure induces oxidative-inflammatory reactions and DNA damage in rats (Danielsen et al, 2010) and increase of biomarkers for inflammation in mouse pulmonary alveolar macrophage (Shang et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Air pollution is comprised of various particulate matters (PMs) that can cause skin diseases, cancer, pulmonary, and cardiovascular diseases [2][3][4]. The increased ambient PM from industrialization and urbanization is highly associated with morbidity and mortality worldwide [2].…”
Section: Introductionmentioning
confidence: 99%
“…The increased ambient PM from industrialization and urbanization is highly associated with morbidity and mortality worldwide [2].…”
Section: Introductionmentioning
confidence: 99%